Prevalence and risk factors for vitamin D insufficiency in 6-12-month-old infants: a cross-sectional study in Southern Thailand - Staporn Kasemsripitak; Somchit Jaruratanasirikul; Sasivara Boonrusmee; Tansit Saengkaew; Hutcha Sriplung (BMC Pediatrics, 2022)
Abstract Background Vitamin D is an essential micronutrient for bone mineralization and bone growth in children. There have been few studies to date of vitamin D status in infants aged 6–12 months in Southeast Asian countries. Aim To examine the prevalence of vitamin D insufficiency (VDI, including vitamin D deficiency) in healthy infants and the risk factors for VDI in southern Thailand. Methods A cross-sectional study was carried out in 120 healthy infants aged 6–12 months and their mothers. Blood samples were obtained for measurement of serum calcium, phosphate, alkaline phosphatase, albumin, parathyroid hormone and 25-hydroxyvitamin D (25OHD) levels. The mothers were interviewed for their infants feeding intake, sunlight exposure, type of dress, and sunscreen use. Chi-square and t-test were used to compare between groups for categorical and continuous variables, respectively. Pearson correlation was used to identify the relationship between serum levels of 25OHD of the infants and other biochemical variables of the infants and serum levels of maternal 25OHD. Logistic regression analysis was used to identify the factors associated with vitamin D status. Results The prevalence of VDI in our study infants was high at 28.3%, all of whom were mainly breastfed infants. Subgroup analysis of the mainly breastfed infants found that the risk factors for VDI were maternal VDI and a short duration of sunlight exposure. The serum 25OHD levels of the mainly breastfed infants were significantly positively correlated with the maternal serum 25OHD levels (r = 0.49, p-value < 0.01) and with sunlight exposure duration (r = 0.40, p-value < 0.01). Conclusions The prevalence of VDI was high in 6–12-month-old infants, particularly those who were mainly breastfed from VDI mothers, and who had short durations of sunlight exposure. As breast milk contains adequate amounts of most important vitamins and growth factors, breastfeeding is still encouraged for infants with 400 IU vitamin D daily supplementation to prevent VDI.